1988
DOI: 10.1159/000205683
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Controlled Study of Androgen Therapy in the Anemia of Chronic Renal Disease: Effects on Iron Kinetics

Abstract: Ferrokinetic and RBC mass determinations were made at 3-month intervals in iron-replete hemodialysis patients randomized to a control group or to nandrolone decanoate therapy. After 3 months, RBC mass increased in two of 4 androgen-treated patients. Erythron iron turnover, an index of RBC production, increased in the one responder studied but not in the two nonresponders. Similarly, in a fifth subject, who was not restudied until 6 months of androgen therapy were completed, an increase in RBC mass was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In a subsequent small study using 59 FE and 51 Cr, these investigators examined the ferrokinetic effects of nandrolone decanoate (6). Androgen-treated patients experienced an increase in RBC mass without an increase in erythron iron turnover or a fall in marrow transit time.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In a subsequent small study using 59 FE and 51 Cr, these investigators examined the ferrokinetic effects of nandrolone decanoate (6). Androgen-treated patients experienced an increase in RBC mass without an increase in erythron iron turnover or a fall in marrow transit time.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…One limitation is the fact that the findings are not generalizable to all patient populations with CKD. Two of the four studies included in this meta-analysis had only male patients over the age of 50, likely because response to androgens has previously been shown to be age related [13] and because of the risk of virilization in females. Androgens may be more effective in older males because of testosterone deficiency in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the intimal mechanism may be mediated by triggering the pluripotential stem cells from the G 0 phase or prolonged G 1 phase into a G 1 interval responsive to EPO (83). Furthermore, the works by Solomon and Hendler based on ferrokinetic data and RBC enzyme determinations (50,51) showed that the increase in RBC mass after administration of ND resulted from two mechanisms: increased erythropoiesis, shown by simultaneous increases in RBC mass and erythron iron turnover; and also increased RBC survival, suggested by an increase in RBC mass without increment in erythron iron turnover.…”
Section: Androgens and Renal Anemiamentioning
confidence: 99%